Sistem Monitoring Dan Evaluasi Order Pada PT. Telkom Akses Devisi Provisioning BGES Magelang - Santoso, Kartika Imam; Satriya, Ilham Jati; Sundari, Cisilia (Jurnal Sistem Informasi (JASISFO), 2022)
With the number of requests for new pairs with an average number of 90 new pairs orders per month, there is a need for continuous evaluation of employee performance and performance related to Time To Delivery orders to ensure the achievement of the goals that have been set. Managers and Leaders have been supervising the performance of Time to Delivery orders and employee performance by asking the DSS (Decision Support System) section which handles BGES order performance data. Then the DSS (Decision Support System) performs a data search to present it in the form of a report to the manager and his staff. This makes Managers and Leaders unable to see employee performance and monitor the handling of new network installations directly. The purpose of this research is to design and build a web-based order monitoring information system at PT. Telkom Access Magelang on the BGES Provisioning division. The system development method used is the Waterfall model. The modeling in the system design used is DFD and ERD modeling while making the website using the PHP programming language, Laravel Framework, and MySQL as database manager. The result of this research is a Monitoring and Evaluation Information System that can provide information about the daily order performance to Managers and Leaders at PT Telkom Access the BGES Provisioning Division.